The city in China : new perspectives on contemporary urbanism - Forrest, Ray; Ren, Julie; Wissink, Bart (Bristol University Press, 2019)
This book gathers together reflections from a broad range of urban China specialists to actively engage with the challenge of conceptualising urban China and ask important questions about the development of contemporary global cities.